The Psi colonization of educational discourse (Foro de Educacion, 2017)
This article reviews the role of psychological discourse in education. On the one hand, the authors criticize the abuse of the mental health diagnosis in the field of education. On the other hand, analyze the effects of the expansion of the neurosciences in the conditions of production of pedagogical knowledge. Finally, examine the role of the neuroeducation and the development of emotional psychology in the construction of enterprising subjectivities. Against these colonizing tendencies of educational discourse, the authors advocate the establishment of a new pedagogical contract that allows rethink the exercise of the educational function of teachers and educators.